Sistem Administrasi Permintaan dan Pengiriman Alat Kesehatan pada PT. Samudra Farma Bengkulu - Asnawati Asnawati; Venny Novita Sari (UNIVED Press, 2017)
This research aims to make the system making demand administration and shipping of medical equipment to the PT. Samudra Farma Bengkulu. With this program are expected to help in providing the data update demands and shipping medical equipment. The method used in this research is the System Development Life Cycle (SDLC). SDLC it serves to illustrate the main stages and steps of each stage are broadly divided into three (3) activities of the analysis, design and implementation, while the proposed methods of data collection are observation, interviews, and literature.The results of this research is a medical equipment data reports, the data demands, acceptance and shipping medical equipment report. The program was created by using Microsoft Access and Microsoft Visual Basic Programming Language 6.0.Keyword : administration, Demand and shipping, Visual Basic 6.0